Crosstalk between focal adhesions and material mechanical properties governs cell mechanics and functions. (1st September 2015) - Fusco, Sabato; Panzetta, Valeria; Embrione, Valerio; Netti, Paolo A.
Graphical abstract: Abstract: Mechanical properties of materials strongly influence cell fate and functions. Focal adhesions are involved in the extremely important processes of mechanosensing and mechanotransduction. To address the relationship between the mechanical properties of cell substrates, focal adhesion/cytoskeleton assembly and cell functions, we investigated the behavior of NIH/3T3 cells over a wide range of stiffness (3–1000 kPa) using two of the most common synthetic polymers for cell cultures: polyacrylamide and polydimethylsiloxane. An overlapping stiffness region was created between them to compare focal adhesion characteristics and cell functions, taking into account their different time-dependent behavior. Indeed, from a rheological point of view, polyacrylamide behaves like a strong gel (elastically), whereas polydimethylsiloxane like a viscoelastic solid. First, focal adhesion characteristics and dynamics were addressed in terms of material stiffness, then cell spreading area, migration rate and cell mechanical properties were correlated with focal adhesion size and assembly. Focal adhesion size was found to increase in the whole range of stiffness and to be in agreement in the overlapping rigidity region for the investigated materials. Cell mechanics directly correlated with focal adhesion lengths, whereas migration rate followed an inverse correlation. Cell spreading correlated with the substrate stiffness on polyacrylamide hydrogel, while no specific trend was found on polydimethylsiloxane. Substrate mechanics can be considered as a key physical cue that regulates focal adhesion assembly, which in turn governs important cellular properties and functions.